Epidemiologic analysis of Leptospira spp. infection among sheep in Pernambuco state, Brazil - Machado, Acidália Claudino; Oliveira, Junior Mário Baltazar De; Silva Júnior, José Lopes Da; Assis, Nivaldo Aparecido De; Brandespim, Daniel Friguglietti; Mathias, Luis Antonio; Mota, Rinaldo Aparecido; Pinheiro Júnior, José Wilton (Instituto Biológico, 2016)
ABSTRACT: This study aimed to analyze epidemiological aspects and spatial characteristics of Lesptospira spp. infection among sheep in Pernambuco state, Brazil. A total of 426 samples were collected from unvaccinated animals aged 1 year or older, and submitted to Microscopic Agglutination Test (MAT). To study the risk factors, a standardized investigative survey of sheep farmers, with objective questions, was conducted to establish the general characteristics of the farm property production, reproductive management, and health plan. From 426 samples analyzed, 83 (19.5%; CI 15.9 - 23.6%) were positive; among them, the most prevalent serovar was Autumnalis (32.4%). Significant differences were observed between gender (OR = 0.38; CI 0.14 - 0.99), production system (OR = 2.03; CI 1.07 - 3.84), types of herd (OR = 2.28; CI 1.39 - 3.72), absence of rodents to the grain storage (OR = 0.55; CI 0.34 - 0.91), and restriction to surface waters (OR = 0.60; CI 0.37 - 0.99). Leptospira spp. infection is disseminated in sheep herds, and multiple factors can influence its occurrence. Health education programs and worker training in prevention and control of leptospirosis and other infectious diseases may be useful to reduce infection rates and economic losses caused by this disease.

RESUMO: Objetivou-se com este estudo analisar os aspectos epidemiológicos e caracterizar espacialmente a infecção por Leptospira spp. em ovinos no estado de Pernambuco, Brasil. Para compor a amostragem do estudo, foram colhidas 426 amostras de animais com idade igual ou superior a um ano, não vacinados, e submetidas à reação de Soroaglutinação Microscópica (SAM). Para o estudo dos fatores de risco, aplicou-se um questionário investigativo padronizado, constituído por perguntas objetivas ao criador, referentes às características gerais da propriedade, ao manejo produtivo, reprodutivo e sanitário. Das 426 amostras analisadas, 83 (19,5%; IC 15,9 - 23,6%) foram positivas; entre elas, o sorovar de maior prevalência foi o Autumnalis (32,4%). Foram observadas diferenças significativas entre sexo (OR = 0,38; I.C. 0,14 - 0,99), sistema de criação (OR = 2,03; I.C. 1,07 - 3,84), tipo de rebanho (OR = 2,28; I.C. 1,39 - 3,72), ausência do acesso de ratos a ração (OR = 0,55; I.C. 0,34 - 0,91) e restrição a águas de superfície (OR = 0,60; I.C. 0,37 - 0,99). A infecção por Leptospira spp. está distribuída nos rebanhos ovinos e são múltiplos os fatores que podem influenciar sua ocorrência. A implantação de programas de educação em saúde e o treinamento da mão de obra em métodos de prevenção e controle da leptospirose e outras doenças infecciosas podem ser úteis na redução dos casos de infecção e na diminuição das perdas econômicas causadas por esta enfermidade.
Análise epidemiológica da infecção por Leptospira spp. em ovinos no estado de Pernambuco, Brasil
Keywords: epidemiology; leptospirosis; sheep industry; epidemiologia; leptospirose; ovinocultura